Antagonistic Evaluation of Trichoderma against The Pathogens Colletotrichum, Pestalotiopsis, and Phytophthora using Dual Culture and Split Plate Techniques - Muhammad Rasyid Hamidy; Widihastuty; Suhanna Ahmad (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Plant pathogens such as Colletotrichum, Pestalotiopsis, and Phytophthora are major causal agents of significant yield losses in tropical horticultural crops. Among various biological control agents, Trichoderma species have been widely studied due to their antagonistic capabilities, rapid colonization, and ability to produce hydrolytic enzymes. Dual-culture and split-plate assays are commonly used to evaluate direct inhibition mechanisms and inhibition mediated by volatile compounds. This study aimed to evaluate the antagonistic potential of Trichoderma reesei against three tropical pathogens using both assay methods. The antagonistic potential of Trichoderma reesei against three major tropical plant pathogens—Colletotrichum gloeosporioides, Pestalotiopsis microspora, and Phytophthora palmivora—was assessed using dual-culture and split-plate techniques. In the dual-culture assay, T. reesei showed varying levels of inhibition across the tested pathogens. The highest mean inhibition was observed against P. microspora (89.37 ± 1.48%), followed by C. gloeosporioides (87.22 ± 2.01%), and the lowest against P. palmivora (84.37 ± 1.35%). Statistical analysis (GLM, F = 9.38; p = 0.0063) revealed significant differences among pathogens, with Tukey's test indicating that inhibition against Pestalotiopsis was significantly greater than against Phytophthora palmivora. The results indicate that Trichoderma reesei exhibits more effective antagonistic activity against Pestalotiopsis than against Phytophthora palmivora. This suggests that the inhibitory mechanisms of T. reesei are more specific and potent against certain pathogens, particularly necrotrophic fungi such as Pestalotiopsis. This specificity enhances its value as a biological control agent by demonstrating selectivity toward target pathogens. Another advantage of T. reesei is its ability to produce hydrolytic enzymes, such as chitinase and glucanase, that degrade the cell walls of pathogens. This enzymatic activity strengthens the effectiveness of biological inhibition without causing negative environmental impacts. Therefore, T. reesei has strong potential as an environmentally friendly alternative to synthetic chemical fungicides. Users are encouraged to integrate T. reesei with Integrated Pest Management (IPM) practices. Combining it with proper cultivation techniques—such as field sanitation, crop rotation, and the use of resistant varieties—will enhance overall disease control effectiveness. Additionally, environmental factors such as humidity, temperature, and soil pH should be considered, as they influence the activity of T. reesei. Optimizing these conditions will improve colonization and antagonistic activity of this microorganism in the field.